STROKE RISK FACTOR ANALYSIS USING STROKE RISK SCORECARDAT RSUD DR. HARJONO S. PONOROGO - Syaiful Nurhidayat; Sulistyo Andarmoyo; Wiwik Widiyati; Dian Laila Purwaningroom (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: Stroke is a condition that occurs when the blood supplay to a part of the brain is suddenly interrupted, because some brain cells die due to disruption of blood flow due to blockage or rupture of brain blood vessels. Death of brain tissue can lead to loss of fungtions controlled by that tissue. Stroke is the main cause of fungtional disorders, where 20% of patients who survive still require treatment at a health institution after 3 months and 15-30% of sufferers experience permanent disability. The introduction of risk factors for stroke is very important, beacause many patients have more than one risk factor and are sometomes ignored, so that the incidence of stroke cannot be avoided. Practical strategies in dealing with the burden of stroke should focus on prevention and treatment based on risk factors. This study is an observational analytic study with a cross-sectional design to determine the relationship between risk factors and the level of risk of stroke patients hospitalized at RSUD dr. Harjono S Ponorogo. This type of research is non-experimental research. This study was conducted in the stroke patient inpatient room.Methods:. The research design used (crosssectional), this sampling technique used consecutive sampling and tabulated data. The sample is 60 respondents. The research instrument uses medical records to view the respondents basic data and medical diagnosis, and the stroke risk scorecard to obtain the results of the assessment of stroke risk factors and the risk level of stroke patients.Results: The results of the study from 60 medical records of stroke patients, risk factors that were proven to have a significant relationship with the level of stroke risk were blood pressure, smoking history, cholesterol levels, history of diabetes. Meanwhile, based on the stroke risk scorecard, the risk level for stroke is mostly high risk.Conclusion: The risk factors that were shown to have a significant relationship with the level of stroke risk based on the results of the distribution table were blood pressure, smoking history, cholesterol levels, history of diabetes. Meanwhile, based on the Stroke Risk Scorecard, the level of stroke risk in stroke patients at Dr. Harjono S Ponorogo Hospital is mostly high risk.